STUDYING THE PROCESS OF DEFORMATION IN THE FLOW MERGER ZONE - Bazarov, Orifjan; Babajanov, Yuldosh; Eshev, Sobir; Kholmamatov, Islom (Innovatsion texnologiyalar, 2024)
Currently, determining the shape of deformable channel channels that do not form a zone of pile formation is one of the urgent problems. In other words, the main requirement in the design and operation of earthen channels is the scientific justification of the shape of the channels that transport water without costs. In this article, based on the conformal reflection method, the erosion that occurs in the confluence zone of open channels and its influence on the flow pattern is studied. It is shown that the hydraulic parameters of the flow depend on the angle at which the channels merge. The problems of canals during the operational period were studied in the process of deformations that occur in the confluence zone of unlined canals, and caused by its influence on erosion.